PENGARUH KOMPETENSI APARATUR DESA, MORALITAS, SISTEM PENGENDALIAN INTERNAL, DAN WHISTLEBLOWING TERHADAP PENCEGAHAN FRAUD DALAM PENGELOLAAN DANA DESA DI KECAMATAN WAJAK - Islamiyah, Faridatul; Made , Anwar; Sari , Ati Retna (Jurnal Riset Mahasiswa Akuntansi, 2020)
The purpose of this research is to examine and explain the influence of village apparatus competence, morality, internal control systems and whistleblowing on fraud prevention in the management of village funds. This research is a quantitative study with a descriptive research design. The data source in this study uses primary data obtained from the results of the distribution of questionnaires to all village officials and village consultative bodies (BPD) of 99 respondents. This research was conducted in Sukoanyar Village, Wajak Village, Sukolilo Village, Blayu Village, and Patokpicis Village in Wajak District. The results of this study indicate that village apparatus competence, morality, internal control systems, and whistleblowing have a significant simultaneous effect on fraud prevention in village fund management. Partially, the competence of the apparatus has a positive influence on fraud prevention in village fund management, morality has a positive influence on fraud prevention in village fund management, the internal control system has a positive influence on fraud prevention in village fund management, and whistleblowing has a positive influence on fraud prevention in managing village funds.